SINTESIS ISOPROPIL SINAMAT DARI SINAMALDEHID PADA MINYAK KAYU MANIS (Cinnamomum cassia) DAN UJI AKTIVITAS SEBAGAI ANTIDIABETES - Anwar, Finalia Femmy; , S.Si., M.Si., Ngadiwiyana; Fachriyah, M.Si, Dra. Enny (Chem Info Journal, 2013)
Has done research on use of synthesis isopropyl cinnamate of cinnamaldehyde in cinnamon oil (Cinnamomum cassia) and test activities as the antidiabetic. The purpose of this study was to isolate cinnamaldehyde of cinnamon oil, synthesis cinnamic acid, cinnamic isopropyl synthesis and test the antidiabetic activity. The method used in this study by using the method of oxidation and esterification through cinnamoil chloride. Analysis of compounds synthesis was using infra red spectrophotometry, gas chromatography-mass pectroscopy. Activity test of anti-diabetic compounds isopropyl cinnamic was with the measurement of inhibition α-glucosidase activity. Cinnamaldehyde which is isolated from cinnamon oil was yellow orange oil and cinnamaldehyde’s yield   1    was up to 76.41% and its purity was 99.87%. Cinnamaldehyde analysis using of infra red spectrophotometer showed carbonyl vibration at 1676 cm-1, C-H aldehyde at 2813.9 cm-1. From mass spectra, it can be known that cinnamaldehyde had M+ 132. Cinnamic acid which is oxidation was a white solid with yield was up to 41,89%. Cinnamic acid analysis using of infra red spectrophotometer showed O-H ad 3433.29 cm-1. Esterification of cinnamic acid chloride sinamoil through using 2-propanol produces brownish yellow liquid with a yield of as much as 84.62% and its purity was 98.43%. Isopropyl cinnamic analysis using of infra red spectrophotometer showed C-O ester at 1165.00 cm-1 and C-O isopropyl at 1111.10 cm-1. From mass spectra, it can be known that isopropyl cinnamic had M+ 190. At concentrations of 74.219 ppm isopropyl cinnamate synthesis results showed activity as antidiabetic of the enzyme that can inhibit α-glucosidase by 96.94% with IC50 value of 45.42 ppm.